Insan Kamil: Ciri dan Proses Pembentukan - Stapa, Zakaria (Afkar: Jurnal Akidah dan Pemikiran Islam, 2001)
Generally, the term of insan kamil is not directly stated in the Qur'an. However, this term is broadly use in the dicipline of tasawuf. Therefore, this article focuses on the concept of insan kamil (the perfect man) based on Ibn 'Arabi views. It is also discusses the criteria of insan kamil.